Persepsi Pelajar Perokok terhadap Penularan Covid-19 di Kecamatan Cibungbulang - Titien Yusnita; Hana Lestari; Anjar Sunarya; Machyudin Agung Harahap; Susri Adeni (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Active smokers and passive smokers are at risk of being infected with COVID-19, causing acute breathing. Existing research results state that smoking habits worsen the health of COVID-19 sufferers so that it affects smoking habits in COVID-19 patients to reduce and even stop smoking (Sabrina & Ichsan, 2021). This study aims to determine how students smoker's perception of the transmission of COVID-19. This research is expected to be able to increase students' knowledge and sense of concern for their own health and the surrounding environment, especially during the COVID-19 pandemic. The research was conducted in Cibungbulang District, Bogor Regency. The research population is students from SMP, SMA and SMK. The sample in this study amounted to 147 students. This study was designed as a survey research using a questionnaire instrument. The design of this study used descriptive quantitative methods with the Pearson Chi-Square correlation test to determine the correlation between variables. The results showed that students' perceptions of COVID-19 transmission in smokers tended to be negative even though the level of student knowledge was categorized as high. This means that students know that COVID-19 can be transmitted to other people including smokers but they do not seek further information about it. Keywords: covid-19, information, students, smokers, perception,